If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 0.4 = 6.4 Reorder the terms: 0.4 + 6x = 6.4 Solving 0.4 + 6x = 6.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.4' to each side of the equation. 0.4 + -0.4 + 6x = 6.4 + -0.4 Combine like terms: 0.4 + -0.4 = 0.0 0.0 + 6x = 6.4 + -0.4 6x = 6.4 + -0.4 Combine like terms: 6.4 + -0.4 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) | | 4n=5-5n | | 88=12x-44 | | 16x-16-8x-12=3 | | 9-4b=4-3b-6b | | 16-(2x-3)=6 | | 6x-14=2(3x-72) | | 11x-13=5(2x+4)-7 | | 45=29-2(x-3) | | 2x^2-y^2-8x+6y-2=0 | | 8a+10=50 | | 7+7k=8k+2 | | -6m+3m=4-m | | 1000=20x+100y | | nsquared+n-105=0 | | 3a-6+7-2a= | | 0.19-0.03(x+1)=-0.02(2-x) | | 9y-187+x+44=180 | | -6n=-9 | | 4x-9x+12=2x+33 | | 8a-13=4a | | r+8=-4r-7 | | 140+0.40=50-0.70 | | 8x+16=-1 | | 25x+25=3(6x+6)+7x+7 | | 2x-7x+60=3x+36 | | 7(2x-3)-4x-20=8(x-1)+3 | | 19=17-2 | | 140+0.40=50+0.70 | | -6p+4+7p=11 | | (y+4)(y+6)= |